Birth-related torts e libertà della donna di interrompere la gravidanza nell’esperienza italiana (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The knowledge about human reproduction and its mechanisms have been improved considerably during the last decades. This is very helpful for lawyers, since science gives them the opportunity to understand more in depth the connections between facts and events, that is essential in birth-related torts.In the meantime, it has been paid greater attention to human rights, and in particular to women fundamental rights. Since 1978, in Italy, it has been possible for women to interrupt pregnancy voluntarily within the first 90 days of gestation. Law 194/78 grants through abortion the respect of women's right to privacy and health.In such a scenario scholars and judges are still divided on tort law application to human reproduction.This article provides a brief introduction to the birth-related torts: wrongful pregnancy wrongful birth and wrongful life. Relying on Italian supreme court case law, for each of them, fundamental elements – such as duty, breach, causation and harm – will be discussed.The article concludes that given some of the recent developments on this subject the approach to wrongful life actions should be re-examined.
Keywords: Wrongful pregnancy; wrongful birth; wrongful life; nascita indesiderata; IVG